Design of a Small-Scale System for the Growth of Artificial Sea Ice - Hall, Benjamin Andrew (Department of Chemical Engineering, 2021)
Sea ice plays a significant role in global climate systems, reflecting a significant portion of solar energy back into the atmosphere and maintaining ocean circulation currents. The effect of climate change on sea ice extent and seasonal changes is as yet unquantified. This is especially true for the initial growth processes and properties within the Antarctic Marginal Ice Zone (MIZ) front during the winter growth season. The Polar Engineering Research Group (PERG) at the University of Cape Town has conducted several research expeditions to the Antarctic MIZ along the 0° line of longitude, collecting samples of first year sea ice. Artificial sea ice has been used as a supplementary area of study because of the advanced control it provides over variables such as cooling rate or initial solution salinity. This allows for the effect of individual variables to be analysed through repeated experiments while adjusting only the variable of interest. Due to the complex nature and conditions of formation for Antarctic sea ice, this study focusses on the key properties of sea ice formed in predominantly calm conditions. These are observed as vertically elongated ice crystals with a c-axis located randomly within the horizontal plane. The profile of ice thickness over time displays a √ x shape. Brine inclusions are located in vertically orientated, interconnected channels, contained within the intracrystalline planes. The crystal planes have spacings of about 1 mm. Lastly, the salinity profile of the ice displays a characteristic c-shaped curve with depth, with higher values of salinity found at the top and bottom of the ice. Ice fitting this description is referred to as columnar S2 ice. The overall aim of this project is to design and test a small-scale system for the growth of artificial sea ice. This system will still enable method development of testing protocols for the testing of the Antarctic sea ice. Once this system has proven to reliably produce saline ice that can be termed as artificial sea ice with a columnar S2 structure, additional design implementations can then be undertaken to accomplish the growth of sea ice that more closely resembles the ice found in the Antarctic MIZ. The system is required to be large enough to produce samples of appropriate size and number to fit the testing protocols for mechanical testing set out by Schwarz et al. (1981), while being statistically sound. Secondary design objectives were to ensure the system is costeffective, portable and simple. A proof of design concept experiment, consisting of a 28 g kg−1 saline solution cooled at at a temperature of - 20 °C, was carried out in order to test the system design. The hypothesis is that the system design will be able to produce saline ice with properties similar to natural sea ice. Temperature profiles and ice growth within the tank were recorded, and ice samples were taken at the end of the run to determine in-ice salinity and crystal morphology. With some refinement of the system to identify the cause of the extended granular and transition layer, the system can be used to provide the necessary test samples for method development for the mechanical testing of sea ice samples collected from the Antarctic MIZ. Following on from this initial design, additional design implementations can be undertaken to accomplish the growth of sea ice that more closely resembles the ice found in the Antarctic MIZ. This will aid in the determination of sea ice properties and studies of the underlying growth processes that cause them.